The Deep Learning Paradigm in Elementary School Bahasa Indonesia: Transforming Language Acquisition through Mindful, Meaningful, and Joyful Learning - Dinar Mahardhika Pratiwi; Unik Ambar Wati (Universitas Muhammadiyah Mataram, 2026)
This article examines the implementation of the deep learning approach in teaching Bahasa Indonesia at the elementary school level, aligned with the guidelines issued by Puskurjar. Utilizing a qualitative literature review method, this study analyses how the core principles of deep learning (mindful, meaningful, and joyful learning) can resolve persistent pedagogical challenges in early language acquisition. The findings reveal that the deep learning approach systematically supports the structured development of six core language skills (listening, speaking, reading, viewing, writing, and presenting) by shifting classroom dynamics from mechanical memorization to authentic linguistic practice. Furthermore, the study outlines four critical roles for educators in fostering a deep learning emotional anchor. Ultimately, this approach successfully bridges abstract linguistic concepts with students’ daily realities, cultivating active, reflective, and sustainable language competencies in elementary school students.